CT Radiation Dose Reduction in Robot-assisted Pediatric Spinal Surgery. Issue 7 (1st April 2017) - Sensakovic, William F.; O'Dell, M. Cody; Agha, Ali; Woo, Raymund; Varich, Laura
Abstract : Study Design: Retrospective consecutive cohort series. Objective: The aim of this study was to develop a low-dose computed tomography (CT) protocol for use in robot-assisted pediatric spinal surgery. Summary of Background Data: CT scans are utilized preoperatively for preoperative planning, by navigation software during robot-assisted surgery, and postoperatively to assess surgical implant placement. Traditionally high radiation doses produced by CT scanning are a concern in the highly radiosensitive pediatric population. Methods: We developed a low-dose protocol using phantom scans. A cohort of patients undergoing CT scanning using the low-dose protocol was collected. Further, a matching cohort of patients who underwent standard scanning was collected. Image quality was assessed by observer ratings. Radiation doses and image quality metrics were compared for the standard and low-dose protocol patients. Results: Effective dose significantly decreased 84% to 91% depending on patient size and whether the scan was preoperative or postoperative. All scans were compatible with the navigation software. No clinically significant differences in image quality were observed between low-dose and standard patient cohorts. Conclusions: Task-based CT protocol optimization can produce acceptable image quality with dose comparable to standard two-view radiography. Level of Evidence: 2